Songket: The Linkage Between Heritage and Tourism in Malaysia - Yusnita, Yusof; Yahaya, Ibrahim; Mat Rahimi, Yusof (2018)
Malaysia is well known for its diversity of cultures and rich heritage. Songket weaving is one of the old crafts that remain popular to this day. Songket is a fabric traditionally woven using silk or cotton, with metallic thread weaved in to form songket motifs. In other words, this means thread is removed or pulled from the back of the weaved cloth using gold or silver thread. The Songket is synonymous with the Malay community, and in Terengganu, making songket is a legacy from the past that is still widely practiced. Interestingly, the songket has also become one of the many symbols used for tourism-related products, representing multi-racial Malaysia in the eyes of the world. This can also be seen in buildings around Malaysia that display the songket motifs. This unique cloth is usually worn as formal wear, such as wedding dresses, costumes for traditional dancers, and robes used in convocation ceremonies. Until today, there are still many songket weavers that produce quality songket as required by nobles, dignitaries, and ministers for use at special ceremonies. This paper aims to identify how far the songket has evolved to become a tourism product in Terengganu and whether this legacy continues among the younger generation. This study uses qualitative methods of face-to-face interviews as well as analysis of secondary data. The results of this study show that the songket draws tourists to Terengganu, and at the same is a source of income for entrepreneurs.